K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

8 tháng 9 2021

`(3 - 1/4 + 2/3)-  (5+1/3 - 6/5) - (6-7/4 + 3/2)`

`= 3 - 1/4 + 2/3 - 5 - 1/3  + 6/5 - 6 + 7/4 - 3/2`

`= (3 - 5 - 6) + ( (-1)/4 + 7/4) + (2/3 -1/3) + 6/5 - 3/2`

`= -8 + 3/2 +1/3 +6/5 - 3/2`

`= (-8 + 1/3 + 6/5) + (3/2-3/2)`

`= (=97)/15`

4 tháng 10 2017

      \(\left(45\frac{1}{2}-2\frac{3}{8}\right)-\left(5\frac{5}{6}+6\frac{3}{4}\right)+\left(10\frac{2}{3}-5\frac{5}{8}\right)\)

\(=\left(\frac{91}{2}-\frac{19}{8}\right)-\left(\frac{35}{6}+\frac{27}{4}\right)+\left(\frac{32}{3}-\frac{45}{8}\right)\)

\(=\frac{345}{8}-\frac{151}{12}+\frac{121}{24}\)

\(=\frac{1035}{24}-\frac{302}{24}+\frac{121}{24}\)

\(=\frac{854}{24}\)\(=\frac{427}{12}\)

8 tháng 7 2023

|7 - \(\dfrac{3}{4}\)\(x\)| - \(\dfrac{3}{2}\) = \(\dfrac{1}{\dfrac{1}{2}}\)

|7 - \(\dfrac{3}{4}x\)|  - \(\dfrac{3}{2}\) = 2

|7 - \(\dfrac{3}{4}\)\(x\)| = 2 + \(\dfrac{3}{2}\)

|7 - \(\dfrac{3}{4}x\)| = \(\dfrac{7}{2}\)

\(\left[{}\begin{matrix}7-\dfrac{3}{4}x=\dfrac{7}{2}\\7-\dfrac{3}{4}x=-\dfrac{7}{2}\end{matrix}\right.\) 

\(\left[{}\begin{matrix}\dfrac{3}{4}x=7-\dfrac{7}{2}\\\dfrac{3}{4}=7+\dfrac{7}{2}\end{matrix}\right.\)

\(\left[{}\begin{matrix}\dfrac{3}{4}x=\dfrac{7}{2}\\\dfrac{3}{4}x=\dfrac{21}{2}\end{matrix}\right.\)

\(\left[{}\begin{matrix}x=\dfrac{14}{3}\\x=14\end{matrix}\right.\)

8 tháng 7 2023

 5  - |\(x-3\)| = 5

       |\(x-3\)| = 5 - 5

      |\(x-3\)| = 0

      \(x-3\) = 0 

      \(x\) = 3

1. Tính hợp lí :

a) \(\frac{6}{7}.\frac{5}{11}+\frac{5}{7}.\frac{2}{11}-\frac{5}{7}.\frac{14}{11}\)

\(=\frac{5}{7}.\left(\frac{6}{11}+\frac{2}{11}-\frac{14}{11}\right)\)

\(=\frac{5}{7}.\frac{-6}{11}=-\frac{30}{77}\)

b) \(\frac{1}{3}.\frac{4}{5}+\frac{1}{3}.\frac{6}{5}-\frac{1}{3}\)

\(\frac{1}{3}.\left(\frac{4}{5}+\frac{6}{5}-\frac{1}{3}\right)\)

\(=\frac{1}{3}.\frac{5}{3}=\frac{5}{9}\)

5 tháng 8 2019

:)))))))))))

17 tháng 9 2016

em nham cau dau tien la (4/5+1/2) : -13/5 + 3/2

9 tháng 7 2018

\(\frac{1}{2}\)\(\frac{2}{3}\)+ (\(\frac{3}{4}\)\(\frac{3}{4}\)) + ( -\(\frac{4}{5}\)\(\frac{4}{5}\)) + ( \(\frac{5}{6}-\frac{5}{6}\)) - \(\frac{6}{7}\)

\(\frac{1}{2}-\frac{2}{3}-0-0-0-\frac{6}{7}\)

\(\frac{1}{2}-\frac{2}{3}-\frac{6}{7}\)

=\(\frac{21}{42}-\frac{28}{42}-\frac{36}{42}\)

\(\frac{-43}{42}\)

9 tháng 7 2018

hjjjjhhbnjbbhhbbb